Human parathyroid hormone fragment stimulates the de novo synthesis of prostaglandin endoperoxide synthase in chick calvaria - Chin-Yuh Yang; Ching-Liang Meng; Patrick Y- K. Wong (Mediators of Inflammation)
The human parathyroid hormone N-terminal fragment [hPTH-(1–34)] increases the conversion of exogenous unsaturated fatty acids to prostaglandins (PGs) in calvarial homogenates. Enzyme activities were completely blocked by indomethacin (5 × 10−7 M), a PG synthase inhibitor, and actinomycin D (5 μM), an inhibitor of transcription, by binding to DNA. In addition, a potent inhibitor of protein synthesis, cycloheximide (10 μM), totally inhibited the stimulating effect of hPTH-(1–34) on prostaglandin endoperoxide synthase (PG synthase, EC 1.14.99.1). The stimulatory effect of hPTH-(1–34) on PG synthase was also reduced by the addition of stannous chloride. However, epidermal growth factor (EGF), platelet-derived activating factor (PDGF), and ionophore A23187 did not show the same stimulating effect as hPTH-(1–34) on PG synthase in calvaria. The results further demonstrated that PG synthase is a membrane-bound enzyme in chick calvaria. In this communication, evidence is presented that hPTH-(1–34) stimulates the de novo synthesis of PG synthase as demonstrated by the increased activity in calvarial homogenates and microsomes.